2009
DOI: 10.1016/j.jff.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, conjugation and efflux of the flavonoids, kaempferol and galangin, using the intestinal CaCo-2/TC7 cell model

Abstract: Flavonoids are biologically active compounds in food with potential health effects. We have used the Caco-2 cell monolayer model to study the absorption and metabolism of two flavonols, a class of flavonoids, specifically kaempferol and galangin. Metabolism experiments allowed identification of 5 kaempferol conjugates: 3-, 7- and 4′-glucuronide, a sulphate and a glucurono-sulphate; and 4 galangin conjugates: 3-, 5- and 7-glucuronides, and a sulphate, using specific enzyme hydrolysis, HPLC-MS, and HPLC with pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 48 publications
4
42
1
Order By: Relevance
“…Kaempferol transfer from both directions was not affected by the application of inhibitors of efflux transporters MRP2. This evidence is indicative of passive transport, and is consistent with a previously published study (Barrington et al, 2009). …”
Section: Transport Studysupporting
confidence: 93%
See 1 more Smart Citation
“…Kaempferol transfer from both directions was not affected by the application of inhibitors of efflux transporters MRP2. This evidence is indicative of passive transport, and is consistent with a previously published study (Barrington et al, 2009). …”
Section: Transport Studysupporting
confidence: 93%
“…Metabolism of kaempferol has been studied previously in Caco-2/TC7 cells (Barrington et al, 2009), and here five metabolites were identified, including a kaempferol glucurono-sulfate.…”
Section: Metabolism Studymentioning
confidence: 77%
“…The cell culture models were proved to be a good alternative for animal studies and have emerged as one of the standard in vitro tools to predict in vivo intestinal absorption of various substances. Subsequently, they were found to be suitable to study intestinal transport of phytochemicals [Barrington et al, 2009;Deprez et al, 2001], and nowadays, cell line models are called an indispensable tool in food science and nutrition [Langerholc et al, 2011]. The studies of epithelial transport/bioavailability are performed in conditions mimicking physiological condi-tions, involving pH 6.0-7.4.…”
Section: Introductionmentioning
confidence: 99%
“…The structurepermeability relationships of some dietary flavonoids including flavonoid agylcone and flavonoid glucoside were investigated using the Caco-2 cell monolayer [9][10][11][12][13]. Most flavonoid glucosides are impermeable to the intestinal barrier; however, flavonoid aglycones (e.g.…”
Section: Introductionmentioning
confidence: 99%